Policies for Promoting the Digital Transformation in Education in Ethnic Minority and Mountainous Areas - Van Chieu, Nguyen; Thanh Lich, Hoang; Tich Nghi, Nguyen (VNU Journal of Science: Policy and Management Studies, 2022)
Digital transformation is an important condition to enhance opportunities for expanding and improving the quality of education in ethnic minority areas. The essence of digital transformation in education is the transformation of content, curricula, and education management based on technology for high socio-economic efficiency at low cost. Digital transformation in education opens up opportunities and contributes to social development in ethnic minority areas. However, this process faces many challenges due to the typically difficult natural and socio-economic conditions of the ethnic minority areas. Therefore, an adequate understanding of digital transformation, as well as accurate assessments of the context in order to achieve sound digital transformation policies of improving the quality and effectiveness of education, are critical for the development of ethnic minority areas. Keywords: policies, digital transformation, education, ethnic minorities